The complete chloroplast genome sequence of Lirianthe hodgsonii, a tree species of Magnoliaceae as least concern - Shao-Yu Chen; Tao Wu; Hui-Fen Ma; Yu-Pin Fu; Yun-Feng Zhu; Jia-Bo Hao; Hong Jiang; Yong-Kang Sima (Mitochondrial DNA. Part B. Resources, 2020)
Lirianthe hodgsonii is a tree species of Magnoliaceae as least concern. In the present paper, the complete chloroplast genome (cpDNA) and basic annotated information of L. hodgsonii were reported and its phylogenetic relationship with other species in Magnoliaceae was analyzed. The size of its complete cpDNA is 159,693 bp, with a typical quadripartite structure comprising a pair of inverted repeat (IR) regions of 26,546 bp, a large single-copy (LSC) region of 87,848 bp and a small single-copy (SSC) region of 18,753 bp. The genome contains 131 unique genes, including 86 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic analysis showed that L. hodgsonii is affinal to Lirianthe bidoupensis and they form a monophyletic group with other seven Lirianthe species. This Lirianthe clade is sister to the Dugandiodendron and Talauma clade with high support. All genera mentioned in this analysis are monophyletic under the system of Magnoliaceae by Sima and Lu.